1982
DOI: 10.1115/1.3227251
|View full text |Cite
|
Sign up to set email alerts
|

Rotor Wake Mixing Effects Downstream of a Compressor Rotor

Abstract: An experimental study of rotor wake was conducted in the trailing-edge and near-wake regions of a moderately loaded compressor rotor blade using a rotating triaxial hot-wire probe in a rotating frame of reference. The flow-field was surveyed very close to the trailing-edge as well as inside the annulus and hub-wall boundary layers. The large amount of data acquired during this program has been analyzed to discern the decay effects as well as the spanwise variation of three components of velocity, three compone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

1985
1985
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…This suggests that the formation of the vortex street is the primary loss-producing mechanism in the wake. A similar result was found by Ravindranath and Lakshminarayana (1982) behind a compressor rotor, although they made no comment on the presence or otherwise of a vortex street.…”
Section: Introductionsupporting
confidence: 68%
“…This suggests that the formation of the vortex street is the primary loss-producing mechanism in the wake. A similar result was found by Ravindranath and Lakshminarayana (1982) behind a compressor rotor, although they made no comment on the presence or otherwise of a vortex street.…”
Section: Introductionsupporting
confidence: 68%
“…The defect in the relative total velocity decreases monotonically with axial distance. However the data of Ravindranath and Lakshminarayana (1982) shows a slight increase in the defect in the trailing edge region and then a monotonical decrease and this is not predicted by the numerical scheme.…”
Section: Wake Decay Characteristicsmentioning
confidence: 78%
“…Some symbols in all figures below need to explain. The symbol “EXP” represents the data come from experiments 28 and “CAL_tra”, “CAL_mix”, “CAL_nn” represent the predicting results based on the traditional loss and deviation models, 5,1321 the spanwise mixing models, 22,23 and the surrogate model developed in this paper, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Schlichting, Das, and Kiock 16,17 found that for the rear stages of compressors, the turbulence intensity increased by about 6%, indicating that mixing cannot be ignored. By measuring the radial turbulence intensity, Lakshminarayana 1821 found that the radial turbulence intensity decayed much more slowly than the tangential and streamwise directions. As a result, he believed that high turbulence levels significantly contribute to spanwise mixing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation